Long‐range correction for density functional theory. (12th August 2014) - Tsuneda, Takao; Hirao, Kimihiko
Abstract : Long‐range correction for exchange functionals in Kohn–Sham density functional theory and its applicability are reviewed. Long‐range correction simply supplements the long‐range exchange effect in exchange functionals by replacing the Hartree–Fock exchange integral with the long‐range part of exchange functionals. Nevertheless, this correction has solved many problems in Kohn–Sham calculations. Using this correction, valence occupied and unoccupied orbital energies are quantitatively reproduced in a comprehensive manner for the first time. Long‐range correction has also solved the underestimations of charge transfer excitation energies and oscillator strengths in time‐dependent Kohn–Sham calculations and has clearly improved poor optical response properties such as hyperpolarizability in coupled‐perturbed Kohn–Sham and finite‐field calculations. Moreover, this correction has drastically improved the reproducibility of van der Waals bonds by simply combining with conventional van der Waals calculation methods. We, therefore, believe that the long‐range correction clearly extends the applicability of the Kohn–Sham method in future quantum chemistry calculations. This article is categorized under: Electronic Structure Theory > Density Functional Theory Abstract :